ANALISIS SISTEM PENGENDALI KAPASITAS BEBAN MUATAN TRUK BERBASIS TEKNOLOGI INTERNET - Zelika Argyanti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
In everyday life, trucks are used to transport goods. Not infrequently seen a lot of use of trucks that exceed the carrying capacity. Accidents on the highway include the impact caused by trucks that are overloaded or overloaded. The purpose of this study is to reduce the risk of accidents due to overloading or overloading. The truck load monitoring system aims to make it easier for truck users to see the truck load weight directly through a smartphone with an application. In addition, users can also see the excess weight of the load and there is an overweight indicator in the form of a buzzer. With this system, users can reduce the risk of accidents on their vehicles. This system consists of a load cell sensor and HX711 module as a weight detector, NodeMCU as a microcontroller and data transmission, firebase as a database, and android studio as a container for creating applications. Payload weight data can be monitored remotely or close according to the principles of the Internet of Things (IoT). The results of this study indicate that the system works well with the sensor accuracy level on the prototype truck 1 and truck prototype 2 above 95%. Writing data on firebase, reading firebase through the application and testing the buzzer has a 100% success rate percentage. There is no diference transmission delay between serial monitor and firebase.